Touch sensation based computer application to facilitate the learning process of dyslexic children - Manoranjitham, M. (American Scientific Publishers, 2017)
The exploration of touch sensation as a learning aide for the visually impaired has gained the attention of many researchers worldwide which leads to more work to be associated with touch sensation. As a part of this effort, the use of touch sensation has been extended to facilitate the learning process of another group of disability. In this study, dyslexic children aged 3 to 8 are studied and their difficulties in educational learning have been identified through an investigation with Dyslexic Awareness of Malaysia (DAM). A thorough research on the existing educational based computer applications shows that the current environment is not suitable and does not contribute in assisting the dyslexic children to perceive knowledge. Thus, in this study, a computer based application incorporating touch sensation as one of the design element has been suggested to improve the entire learning experience of dyslexic children. This application gives an illusion force when the students interact using the application to learn some alphabets. The initial empirical results a positive feedback encouraging the effort of introducing touch sensation to the dyslexic children to be a beneficial suggestion. © 2017 American Scientific Publishers. All rights reserved.